1987
DOI: 10.1111/j.1365-2672.1987.tb02683.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties of lactobacilli isolated from the small intestine of pigs

Abstract: One hundred wild-type strains of the genus Lactobacillus were isolated from the small intestine of newly-slaughtered pigs up to 6 months of age. Cell surface hydrophobicity and capsule formation were studied on a number of strains. Strains showing high surface hydrophobicity as measured by the salt-aggregation test and hydrophobic interaction chromatography on Octyl Sepharose were commonly found to adhere in high numbers to isolated pig intestinal epithelial cells. Heat and protease treatment of bacteria of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
97
2
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 21 publications
8
97
2
1
Order By: Relevance
“…The composition, structure and forces of interaction related to bacterial adhesion to intestinal epithelial cells have been investigated by several workers and obtained a relation between cell adherence and its close interaction with undesirable bacteria (Boris et al, 1997;Re et al, 2000;Ehrmann et al, 2002). Surface hydrophobicity examined in the present study illustrate probable interrelation between the physico-chemical property of test strain and their ability to adhere to the intestinal mucus as proposed by Wadstrom et al, 1987. The present result showed a high percentage of B. cereus cells adhered to xylene, an apolar solvent and toluene which demonstrate hydrophobic cell surface property of this strain.…”
Section: Resultsmentioning
confidence: 65%
“…The composition, structure and forces of interaction related to bacterial adhesion to intestinal epithelial cells have been investigated by several workers and obtained a relation between cell adherence and its close interaction with undesirable bacteria (Boris et al, 1997;Re et al, 2000;Ehrmann et al, 2002). Surface hydrophobicity examined in the present study illustrate probable interrelation between the physico-chemical property of test strain and their ability to adhere to the intestinal mucus as proposed by Wadstrom et al, 1987. The present result showed a high percentage of B. cereus cells adhered to xylene, an apolar solvent and toluene which demonstrate hydrophobic cell surface property of this strain.…”
Section: Resultsmentioning
confidence: 65%
“…Lactobacilli with high autoaggregation ability showed high hydrophobicity (Chen et al, 2010;Nikolic et al, 2010). Previous studies indicated a correlation between adhesion ability and hydrophobicity of some lactobacilli (Wadstroum et al, 1987;Xu et al, 2009). Mainly cell surface-associated proteins are involved in aggregation and adhesion although many other factors existed like teichoic, lipoteichoic acids, and polysaccharide (Goh and Klaenhammer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Adherence of bacterial cells is usually related to cell surface characteristics (Bibiloni et al 2001;Canzi et al 2005). Physicochemical characteristics of the cell surface such as hydrophobicity may affect autoaggregation and adhesion of bacteria to different surfaces (Wadström et al 1987;Perez et al 1998;Del Re et al 1998). Autoaggregation ability test together with cell-surface hydrophobicity and coaggregation could be used for preliminary screening identifying potentially adherent bacteria with properties suitable for commercial purposes (Vlkova et al 2008;Collado et al2008).…”
Section: Introductionmentioning
confidence: 99%